The Role of Parents in Developing the Speaking Skills of Children Aged 5-6 Years in Sei Belutu Village - Rawaty Sirait; Suri Handayani Damanik (Asian Journal of Applied Education (AJAE), 2024)
In Sei Belutu Village, Sei Bamban District, Serdang Bedagai Regency, research was conducted to determine the influence of parents on the development of their children's speaking abilities. Descriptive qualitative research was used in this research. In this research, 7 parents and 7 children from Sei Belutu Village, Sei Bamban District, and Serdang Bedagai Regency were research subjects. Research findings come from parent interviews and child observation methodology. According to the findings above, children's speaking abilities are more advanced in the semantics section, and parents play a greater role in the modeling (for example) and teaching (teaching) sections to help children aged 5-6 years develop their speaking skills in Sei Belutu Village.